2001
DOI: 10.1523/jneurosci.21-19-07831.2001
|View full text |Cite
|
Sign up to set email alerts
|

Incentive Sensitization by Previous Amphetamine Exposure: Increased Cue-Triggered “Wanting” for Sucrose Reward

Abstract: We reported previously that an amphetamine microinjection into the nucleus accumbens enables Pavlovian reward cues in a conditioned incentive paradigm to trigger excessive instrumental pursuit. Here we show that sensitization caused by previous amphetamine administration also causes reward cues to trigger excessive pursuit of their associated reward, even when sensitized rats are tested in a drug-free state. Rats learned to lever press for sucrose pellets, and they separately learned to associate sucrose pelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
279
1
6

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 395 publications
(324 citation statements)
references
References 64 publications
38
279
1
6
Order By: Relevance
“…Indeed, a recent transfer study found that Pavlovian cues associated with passive intravenous cocaine delivery have the ability to provoke cocaine seeking in rats (LeBlanc et al, 2012). Furthermore, studies using a food-motivated version of the transfer task have shown that rats given repeated exposure to psychostimulants exhibit heightened levels of cuetriggered food seeking (Leblanc et al, 2013a;LeBlanc et al, 2013b;Saddoris et al, 2011;Wyvell and Berridge, 2001), suggesting that these drugs cause long-lasting alterations in the neural substrates of Pavlovian incentive motivation. The current findings indicate that this behavioral influence of Pavlovian learning critically depends on cholinergic signaling through muscarinic and nicotinic receptors, suggesting that drug-induced adaptations in the cholinergic system may contribute to compulsive drug seeking by augmenting the influence of Pavlovian cues.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a recent transfer study found that Pavlovian cues associated with passive intravenous cocaine delivery have the ability to provoke cocaine seeking in rats (LeBlanc et al, 2012). Furthermore, studies using a food-motivated version of the transfer task have shown that rats given repeated exposure to psychostimulants exhibit heightened levels of cuetriggered food seeking (Leblanc et al, 2013a;LeBlanc et al, 2013b;Saddoris et al, 2011;Wyvell and Berridge, 2001), suggesting that these drugs cause long-lasting alterations in the neural substrates of Pavlovian incentive motivation. The current findings indicate that this behavioral influence of Pavlovian learning critically depends on cholinergic signaling through muscarinic and nicotinic receptors, suggesting that drug-induced adaptations in the cholinergic system may contribute to compulsive drug seeking by augmenting the influence of Pavlovian cues.…”
Section: Discussionmentioning
confidence: 99%
“…Typically measured through deficits in motor performance or the occurrence of behavioral stereotypies (e.g., refs. [3,53]), such effects have become hallmarks of psychostimulant exposure even when they carry a simultaneous reward value [63]. Conversely, amphetamine treatment induced an exploratory response (which was at times interrupted by ventral side grooming bouts) wherein crayfish appeared to become 'channeled' into using their antennae to investigate the aquarium perimeter.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a dose of amphetamine that elevates tonic dopamine actually amplifies the neural encoding of phasic 100-ms learned reward cue-triggered signals in the ventral pallidum (which probably reach ventral pallidum via nondopamine afferent projections) that convey learned information about future reward (Tindell et al 2006). Similarly, tonic dopamine elevation by amphetamine elevates behavioral performance triggered by reward cues or directed toward obtaining them (in ways that are too specific to the learned motivating value of cues to be explained by tonic activation or general response strengthening effects of a drug; Cardinal et al 2002;Everitt et al 2001;Everitt et al 1999;Wyvell and Berridge 2001). In short, tonic dopamine affects reward learning and learned performance, involving complexities that might not be expected from a pure focus on phasic dopamine signals.…”
Section: Dopamine-beyond Learning Too?mentioning
confidence: 99%
“…Defined as a want for something you neither like nor expect to like, strongly irrational desire may be rare but does exist (the electrode cases above might be examples). In animal experiments, irrational 'wanting' has been suggested to be created through activation of brain dopamine-related systems via systemic or intra-accumbens amphetamine administration and by psychostimulant-induced neural sensitization of accumbens-related systems (Flagel et al 2007;Peciña et al 2003;Tindell et al 2005;Uslaner et al 2006;Vezina 2004;Wyvell and Berridge 2001). In humans, drug-induced irrational 'wanting' has been suggested to occur via incentive sensitization in some drug addicts, which may create a motivational compulsion to take drugs again even if a drug is not particularly pleasant and even after recovery from withdrawal (Robinson and Berridge 1993;Robinson and Berridge 2003).…”
Section: Dopamine-beyond Learning Too?mentioning
confidence: 99%